2018
DOI: 10.3390/ijerph15102163
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization in a Large Cohort of Asylum Seekers Entering Western Europe in 2015

Abstract: During the current period of immigration to Western Europe, national healthcare systems are confronted with high numbers of asylum seekers with largely unknown health status. To improve care taking strategies, we assessed healthcare utilization in a large, representative cohort of newly arriving migrants consisting of n = 1533 residents of a reception center in Northern Germany in 2015. Most asylum seekers were young, male adults, and the majority came from the Eastern Mediterranean region. Overall, we observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
7
26
1
1
Order By: Relevance
“…This can only in part be explained through pregnancies and birth, as it holds true for almost all diagnosis groups and rates of health care services. These findings replicate other reports [21,67,68]. This might point towards lower access barriers for migrant women or higher health care needs, but we found no published research regarding this topic.…”
Section: Gender Gapsupporting
confidence: 88%
“…This can only in part be explained through pregnancies and birth, as it holds true for almost all diagnosis groups and rates of health care services. These findings replicate other reports [21,67,68]. This might point towards lower access barriers for migrant women or higher health care needs, but we found no published research regarding this topic.…”
Section: Gender Gapsupporting
confidence: 88%
“…In general, available evidence on refugees’ health care needs is primarily focused on needs related to mental health problems (Giacco et al 2018 ; Nesterko et al 2020 ), as well as chronic (Goosen 2014 ) and infectious diseases (Yun et al 2012 ). However, despite numerous reports indicating higher symptom burden, and in consequence increased needs for health care in different refugee populations, data on refugees’ health care needs and/or utilization remains inconsistent (Wetzke et al 2018 ; Yang and Hwang 2016 ). This might be attributable to the great heterogeneity within refugee populations (e.g., due to countries of origin, flight route and duration, exposure to different traumatic events before, during, and/or after the flight) on the one hand, and differences in health policies towards asylum-seekers in different host countries on the other.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the legal and bureaucratic barriers described above, there are factors on the individual level such as age and sex that influence health care needs and utilization in different refugee populations. In Germany, Wetzke et al ( 2018 ) found higher healthcare utilization in refugee children age 10 and under as well as in refugees age 60 and older. Moreover, reports fairly consistently indicate that female refugees utilize health care more often than males do (Bozorgmehr et al 2015 ; Gerritsen et al 2006 ; Henjum et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This issue also documents how migrants and refugees access health services and some of their health care outcomes [26,27,28,29,30,31,32,33,34,35]. Studies in this special issue emphasize the need for well-structured policies and guidelines in the EU to ensure the proper integration of AS and refugees within health systems.…”
Section: Review Of Articles In the Special Issuementioning
confidence: 99%